(untitled) - Seagrave, Chris (Oxford, 1988)
This is a practical guide for owners and managers of still waters and rivers, whether they are used for fisheries, conservation, recreation, or ornament. It is designed to help each reader to take into account many factors apart from actual control techniques before formulating his or her own management strategy. The book deals with fundamental biology, weed growth and management, and the identification, characteristics and control of those weeds which cause most problems. Useful appendices complete a book which will repay its cost many times for owners and managers, while students of agriculture and horticulture as well as fisheries will also find it invaluable.
Keywords: Aquatic weeds,Weed control,Aquatic weeds; Control measures